Prognostic Value of 18F-FDG PET/CT—Metabolic Parameters at Baseline and Interim Assessment in Pediatric Anaplastic Large Cell Lymphoma. (March 2020) - Mathew, Boon; Vijayasekharan, Kalasekhar; Shah, Sneha; Purandare, Nilendu C.; Agrawal, Archi; Puranik, Ameya; Prasad, Maya; Narula, Gaurav; Banavali, Shripad; Rangarajan, Venkatesh
Abstract : Introduction: The event-free survival in pediatric anaplastic large cell lymphoma (ALCL) remains at 70% irrespective of the diverse chemotherapy regimens used. There is lack of valid prognostic factors identifying high-risk patients. We investigated the prognostic value of baseline metabolic parameters and interim response on 18 F-FDG PET/CT in pediatric ALCL patients. Methods: We retrospectively reviewed 40 pediatric ALCL patients with paired 18 F-FDG PET/CT and treated uniformly on vinblastine-based institution protocol. The SUVmax, SUVmean, metabolic tumor volume (MTV), and total lesion glycolysis of the lymphomatous lesion were measured. Continuous PET parameters were stratified by their median values. Deauville scoring system was used to assess response to chemotherapy in the interim scan. Prognostic factors for overall survival (OS) and disease-free survival (DFS) were estimated using the Kaplan-Meier method, log-rank test, and Cox proportional hazards model. Results: At median follow-up of 52 months, 13 patients died and 13 had recurrence. On univariate analysis, higher whole-body MTV (WBMTV) and partial response on interim scan were statistically associated with OS. High-risk features, WBMTV, and partial response were statistically associated with DFS. On multivariate analysis combining baseline characteristics and interim response, interim response (hazard ratio, 3.56; P = 0.034) was statistically significant for OS. Multivariate analysis for DFS using only baseline characteristics revealed WBMTV as statistically significant (hazard ratio, 4.08; P = 0.035), but none of the parameters was statistically significant when baseline characteristics and interim response were evaluated together. Conclusions: Whole-body tumor burden assessment with MTV and interim response may help to identify high-risk patients who might get benefitted from intensive therapy.